Analysis of Influencing Factors on Noise Reduction Effect of High-Speed Railway Sound Barrier. (March 2019) - Sun, Wenjuan; Su, Qiaoping; Yuan, Hongli
Abstract: As an effective and economical noise reduction measure, sound barrier has been widely recognized and applied in the research field of high-speed railway noise reduction. The equivalent sound source height corresponding to the two different sound barrier forms of subgrade and bridge are analyzed by the empirical formula calculation method, and the influencing factors of noise reduction effect of high-speed railway are analyzed. Some referential conclusions is obtained.